2007
DOI: 10.1007/s10558-007-9037-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Ageing on Rising Edge Characteristics of the Photoplethysmogram using a Modified Windkessel Model

Abstract: Ageing is one of the main contributing factors towards increasing arterial stiffness, leading to changes in peripheral pulses propagation. Therefore the characteristics of the photoplethysmogram (PPG) pulse, especially the rising edge and peak position, are greatly affected. In this study, the PPG pulse rising edge and corresponding peak position have been investigated non-invasively in human subjects as a function of age. Fifteen healthy subjects were selected and grouped in five age intervals, from 20 to 59 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 31 publications
4
43
0
Order By: Relevance
“…Whereas, in the majority of the studies this parameter was suggested as a blood pressure surrogate, PTT has gradually become a popular index of arterial stiffness (Kingwell et al 1997;Nichols 2005). Most importantly, pulse transit time has been used as a measure of vascular health and condition across life span (Safar et al 2003;Vaitkevicius et al 1993;Zahedi et al 2007) in different populations (Foo and Lim 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, in the majority of the studies this parameter was suggested as a blood pressure surrogate, PTT has gradually become a popular index of arterial stiffness (Kingwell et al 1997;Nichols 2005). Most importantly, pulse transit time has been used as a measure of vascular health and condition across life span (Safar et al 2003;Vaitkevicius et al 1993;Zahedi et al 2007) in different populations (Foo and Lim 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The valley between these two waves is called dicrotic notch. The location of the dicrotic notch changes from subject to subject and also depends on the age [18]. This prevents the use of simple threshold to detect systolic peaks as compared to peak detection in ECG.…”
Section: Algorithm Description 21 Overviewmentioning
confidence: 99%
“…Next PPG signals were band-pass filtered (0.6-15 Hz) for removing the effect of the respiratory rhythm and higher frequency disturbances. These filters did not introduce phase delays or distortion to the waveforms [8]. A process of beat-by-beat pulse foot identification took place for best pulse selection.…”
Section: Data Processingmentioning
confidence: 99%
“…Pulse foot was taken as the minimum value of the pulse for scaling the PPG AC amplitudes [8], systole point was determined as the maximum point of the pulse, dicrotic notch is determined as the third derivative's first negative to positive zero crossing point which occurred after the third derivative's positive to negative zero crossing point [5]. To ease visualization and comparison, the PPG AC amplitude normalization was done.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation